Islamic Republic of Iran : 2011 Article IV Consultation: Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Iran. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The Iranian economy recovered on the strength of international oil prices, strong rebound in agricultural sector, and rapid credit expansion. Inflation was contained while fiscal and external positions improved. Key policy priorities are to maintain short-term macroeconomic stability, transition to a market-based economy to foster growth, and support job creation; and strengthen the financial sector. The economic reform strategy, anchored in privatization, reduction of the role of government, and market-based prices for energy and agricultural goods should help achieve higher growth and create jobs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet